-L-Band Ring Erbium Doped Fiber Amplifier with Fiber Bragg Grating - S.W, Harun; N, Tamchek; T.C, Teyo; P, Poopalan; H, Ahmad (Malaysian Journal of Science, 2002)
An optical gain-clamped long wavelength band (1570 Ã¢â‚¬â€ 1610 nm) erbium-doped fibre amplifier (L-band EDFA) is demonstrated using a fiber Bragg grating. It uses a counter propagating ring resonator, in order to achieve constant gain with minimum gain variation. The clamped-gain Level can be controlled to be in the range from 7.2 to 14.3dB by increasing the cavity loss from 0 to 20dB. It is found that at 10dB variable optical attenuator (VOA) loss, clamping of the gain is flat with variation of input signal power from Ã¢â‚¬â€40 to Ã¢â‚¬â€5dBm. The gain measured is 10.9dB, which is 30% less than the open ring gain of 15.3dB at a pumping power of 92mW. The noise figure measured is about 52dB. The proposed design prevents oscillating light from being coupled out, but it degrades the amplifierÃ¢â‚¬â„¢s noise figure and clamped gain as the dynamic range is increased.